2008
DOI: 10.1002/eji.200738035
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐tumoral Salmonella typhimurium induces a systemic anti‐tumor immune response that is directed by low‐dose radiation to treat distal disease

Abstract: Salmonella typhimurium is a facultative anaerobic bacterium able to multiply preferentially in tumors and inhibit their growth. The mechanisms through which Salmonella exerts its anti-cancer properties are not fully understood. We recently showed that intra-tumoral Salmonella injection results not only in the regression of even bulky tumor masses, but also impacts on the growth of distant untreated lesions. Here we describe how Salmonella exerts its systemic anti-cancer effects and means to potentiate them. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…However, tumors grew back after treatment withdrawal. These studies demonstrate that imiquimod therapy not only stimulates proinflammatory cytokines and augments Agspecific CD8 + T cells, but also stimulates the proliferation of The observation that acute inflammation can lead to tumor destruction has been previously reported for a variety of local treatments, such as intratumoral bacterial/viral injection, cytokine injection, and cryoablation (27)(28)(29). All of these treatments have been shown to induce intratumor inflammation that favors crosspriming of tumor Ags and upregulation of MHC I.…”
Section: Discussionsupporting
confidence: 53%
“…However, tumors grew back after treatment withdrawal. These studies demonstrate that imiquimod therapy not only stimulates proinflammatory cytokines and augments Agspecific CD8 + T cells, but also stimulates the proliferation of The observation that acute inflammation can lead to tumor destruction has been previously reported for a variety of local treatments, such as intratumoral bacterial/viral injection, cytokine injection, and cryoablation (27)(28)(29). All of these treatments have been shown to induce intratumor inflammation that favors crosspriming of tumor Ags and upregulation of MHC I.…”
Section: Discussionsupporting
confidence: 53%
“…The results of the present study, which demonstrated that a low-dose of priming radiation was able to trigger the NK cytotoxic function, suggested that the therapeutic efficacy may be increased by the augmentation of NK cytotoxic function. The present and previous study results confirmed that stimulation of the antineoplastic immune surveillance was mediated by NK lymphocytes, at least partially, and the accumulating experimental evidence indicated that low-level exposure to low LET radiation inhibited tumor development (21,22).…”
Section: Discussionsupporting
confidence: 89%
“…The efficacy of Salmonella to target and eradicate growing tumors has been well documented. 2,4,5 However, colonization and persistence of Salmonella within healthy tissues weaken its therapeutic efficacy and causes undesirable adverse effects. 3,26 Therefore, it became necessary to develop novel methods to boost the tumor tropism of Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Colony-forming units (cfus) were determined for each transformant with or without isopropyl-L-thio-beta-Dgalactopyranoside induction and were verified after each experiment.…”
Section: Bacteria and Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation